Pengaruh Tahfidz Al-Qur’an terhadap Kecerdasan Emosional dan Kecerdasan Spritual Anak : (Studi Siswa Sekolah Menengah Pertama Swasta Islam Terpadu Pondok Pesantren Al-Furqan Tebas Kabupaten Sambas) - Juwita Juwita; Ubabuddin Ubabuddin; Wulan Purnamasari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to: (1) Describe and analyze the influence of memorization of the Qur'an on the emotional intelligence of students at the Integrated Islamic Private Middle School of Al-Furqan Tebas Islamic Boarding School, Sambas Regency, (2) Describe and analyze the influence of memorization of the Qur'an on the spiritual intelligence of students at the Integrated Islamic Private Middle School of Al-Furqan Tebas Islamic Boarding School, Sambas Regency. This study is a descriptive quantitative study with a causal associative research type (cause and effect). In this study, there are 3 variables, namely the first variable is memorization of the Qur'an, the second variable is emotional intelligence and the third variable is students' spiritual intelligence. The population with research subjects are 40 students of class VIII of the Integrated Islamic Private Middle School of Al-Furqan Tebas Islamic Boarding School. Data collection using the questionnaire method. Instrument validity test using the product moment analysis technique, while reliability test using the alpha coefficient. The data analysis technique used multiple regression analysis. Prior to data analysis, a normality test was conducted. The results of the study indicate that: (1) There is a positive and significant effect of Quran memorization on emotional intelligence, with a magnitude of 0.388 (38.8%), with the remainder influenced by other factors. (2) There is a positive and significant effect of Quran memorization on spiritual intelligence, with a magnitude of 0.376 (37.6%), with the remainder influenced by other factors.